2014
DOI: 10.1002/ptr.5198
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Regulates Skin Photoaging in UVB‐exposed Fibroblast and Hairless Mice

Abstract: Ultraviolet (UV) radiation is the primary factor in skin photoaging, which is characterized by wrinkle formation, dryness, and thickening. The mechanisms underlying skin photoaging are closely associated with degradation of collagen via upregulation of matrix metalloproteinase (MMP) activity, which is induced by reactive oxygen species (ROS) production. Gallic acid (GA), a phenolic compound, possesses a variety of biological activities including antioxidant and antiinflammatory activities. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 47 publications
(58 reference statements)
5
107
0
1
Order By: Relevance
“…Matrix metalloproteinases is a major collagenolytic enzyme responsible for collagen damage in UV‐irradiated human skin 10. Compared with the normal group, both MMP‐1 and MMP‐3 levels in NHDFs were markedly elevated because of UVB irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix metalloproteinases is a major collagenolytic enzyme responsible for collagen damage in UV‐irradiated human skin 10. Compared with the normal group, both MMP‐1 and MMP‐3 levels in NHDFs were markedly elevated because of UVB irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Reverse transcription (RT)‐PCR were performed in a Veriti Thermal Cycler (Applied Biosystems, Foster City, CA, USA) according to our previous research 10. PCR products were stained with ethidium bromide and separated by 2.0% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…UV is the main external factor that causes oxidative stress, such as ROS [27]. ROS simultaneously triggers a series of cascade reactions, eventually leads to overexpression of MMP-1 and degradation of type I procollagen, revealed in photoaging [28].…”
Section: Effect Of Agnps On Dpph Activitymentioning
confidence: 99%
“…MMP is a major collagenolytic enzyme responsible for collagen damage in the UVB-irradiated human skin [27]. Reports suggested that collagen damage due to MMP is a major contributor to the photoaging of human skin [36][37][38][39].…”
Section: Inhibitory Effect Of S-agnps On the Production Of Mmp-1 And mentioning
confidence: 99%
See 1 more Smart Citation